2022
DOI: 10.1111/resp.14246
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of chemical composition on the lung cell response to coal particles: Implications for coal workers' pneumoconiosis

Abstract: Background and objective Coal mine dust has a complex and heterogeneous chemical composition. It has been suggested that coal particle chemistry plays a critical role in determining the pathogenesis of coal workers' pneumoconiosis (CWP). In this study, we aimed to establish the association between the detrimental cellular response and the chemical composition of coal particles. Methods We sourced 19 real‐world coal samples. Samples were crushed prior to use to minimize the impact of particle size on the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Although the sample of CD obtained by grinding coal was from a specific region, it represents the essential composition of CD. The essential composition of CD samples from different geographic sites is coal particles containing the main elements C, H, N, S, O, and the most abundant inorganic constituents SiO 2 and Al 2 O 3 (Su et al, 2020;Song et al, 2022), which is consistent with our results (Figure 1(b); Table 1). Besides, the CD particles of less than 2 μm (Figure 1(a)) can almost all deposit in the tracheobronchial and alveolar areas, and then produce lung toxicity resulting in difficulty of exhalation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the sample of CD obtained by grinding coal was from a specific region, it represents the essential composition of CD. The essential composition of CD samples from different geographic sites is coal particles containing the main elements C, H, N, S, O, and the most abundant inorganic constituents SiO 2 and Al 2 O 3 (Su et al, 2020;Song et al, 2022), which is consistent with our results (Figure 1(b); Table 1). Besides, the CD particles of less than 2 μm (Figure 1(a)) can almost all deposit in the tracheobronchial and alveolar areas, and then produce lung toxicity resulting in difficulty of exhalation.…”
Section: Discussionsupporting
confidence: 91%
“…Of course, the biological processes induced by CD are complex because of its physical and chemical properties. Both the particle size and elemental composition all have an impact (Zhang et al, 2021; Song et al, 2022), including the genotoxicity and cellular transformation effects we found. Therefore, further research is needed on CD itself and its induced pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…qRT‐PCR results showed significant downregulation of PSMB9 mRNA level in mouse lung tissues at day 7, 14, and 28 after silica exposure in a time‐dependent manner. The pathological process of pneumoconiosis involves multiple cell types, of which epithelial cells and myofibroblasts are the two main types 40,41 . To investigate the role of PSMB9 in CWP in vitro, we treated human epithelial cells (HBE or A549 cells) with standard silica powder and activated human lung fibroblasts (MRC‐5) by using human recombinant TGF‐β1.…”
Section: Resultsmentioning
confidence: 99%
“…The pathological process of pneumoconiosis involves multiple cell types, of which epithelial cells and myofibroblasts are the two main types. 40,41 To investigate the role of PSMB9 in CWP in vitro, we treated human epithelial cells (HBE or A549 cells) with standard silica powder and activated human lung fibroblasts (MRC-5) by using human recombinant TGF-β1. The PSMB9 mRNA expression level was then measured via qRT-PCR.…”
Section: Silica Treatment Downregulated the Expression Of Psmb9 In Vi...mentioning
confidence: 99%
“…Existing literature has focused on the development of pulmonary fibrosis in pneumoconiosis, largely examining the role of fibroblasts in the development of CWP [76][77][78]. Instead of merely examining the role of fibroblasts, we assessed the impact of coal-based PM10 on epithelial (A549), neutrophilic (HL-60), and macrophage (THP-1) cells.…”
Section: In Vitro Inflammatory Responsementioning
confidence: 99%